Using association rules analysis to determine favorable mineralization sites in the Jiaojia gold belt, Jiaodong Peninsula, East China - Mao, Xiancheng; Tang, Miao; Deng, Hao; Chen, Jin; Liu, Zhankun; Wang, Jinli (Frontiers in Earth Science, 2023)
Fractured alterated-type gold deposits in the Jiaojia goldfield have long captivated the attention of geologists. Although metallogenic patterns, such as the 'ladder mineralization model in the northwest of Jiaozhou,' have been summarized, these theories have remained qualitative. This study aims to use association rule analysis with spatial constraints to quantitatively identify favorable mineralization sites within the Jiaojia gold ore field. The first favorable mineralization site is located in the footwall of the Jiaojia fault between depths of 3.03 m and 21.82 m, with a slope gradient ranging from -23.38 to -1.48 degrees. The second favorable mineralization site is situated between depths of 21.82 m and 54.06 m in the footwall of the Jiaojia fault, with a secondary fluctuation trend ranging from 6.52 m to 35.1 m. The third favorable mineralization site is found between depths of 54.06 m and 515.83 m in the footwall of the Jiaojia fault, with a secondary fluctuation trend ranging from 0.47 m to 6.14 m and a slope gradient between 31.13 and 35.81 degrees. The proportions of mineralization in the three sites are 44.47%, 45.35%, and 44.44% respectively. The application of the association rule analysis in identifying favorable mineralization sites has shed new light on the regulatory role of the Jiaojia fault in controlling mineralization processes. Through a quantitative assessment of the impact of ore controlling factors on distribution and formation of mineralization, this study reveal the complex correlations between geologic structures and ore deposition. It would contribut to a deeper understanding of the underlying mechanisms governing the formation of fractured alterated-type gold deposits in the Jiaojia goldfield.